Field strength dependence of grey matter R2* on venous oxygenation - Croal, Paula L.; Driver, Ian D.; Francis, Susan T.; Gowland, Penny A. (Elsevier, 2016)
The relationship between venous blood oxygenation and change in transverse relaxation rate (ΔR2 *) plays a key role in calibrated BOLD fMRI. This relationship, defined by the parameter β, has previously been determined using theoretical simulations and experimental measures. However, these earlier studies have been confounded by the change in venous cerebral blood volume (CBV) in response to functional tasks. This study used a double-echo gradient echo EPI scheme in conjunction with a graded isocapnic hyperoxic sequence to assess quantitatively the relationship between the fractional venous blood oxygenation (1-Yv) and transverse relaxation rate of grey matter (ΔR2 * GM), without inducing a change in vCBV.